Unpopular Culture - Luthe, Martin; Pohlmann, Sascha (Televisual culture, 2016)
This collection includes eighteen essays that introduce the concept of unpopular culture and explore its critical possibilities and ramifications from a large variety of perspectives. Proposing a third term that operates beyond the dichotomy of high culture and mass culture and yet offers a fresh approach to both, these essays address a multitude of different topics that can all be classified as unpopular culture. From David Foster Wallace and Ernest Hemingway to Zane Grey and fan fiction, from Christian Rock and Country to Black Metal, from Steven Seagal to Genesis (Breyer) P-Orridge, fromThe Simpsons to The Real Housewives, from natural disasters to 9/11, from thesis hatements to professional sports, these essays find the unpopular across media and genres, and they analyze the politics and the aesthetics of an unpopular culture (and the unpopular in culture) that has not been duly recognized as such by the theories and methods of cultural studies.